Explorer les politiques de la langue et de l’infrastructure - Leandro Rodriguez Medina; David Dumoulin Kervran (Revue d'anthropologie des connaissances)
Analysing how journals operate is fundamental to understand how the academic world works, at a time when the impact factor has become a major sign of research quality. The science studies journal Tapuya was launched in 2016 in Latin America, with the particularity of publishing articles in English in order to raise the profile of research from this continent. This interview with the founder and former editor-in-chief, Leandro Rodriguez Medina, provides a detailed analysis of the political dimension of choices regarding the financial, technological and evaluation process aspects. The first part looks back at the original idea and the journal's model, to see how it is possible to play with the influence of English-speaking countries. The second part explores the various implications of the choice of English as the language of publication, evaluation and work within the journal. The third part examines the various sequences in the work on the articles submitted, to show how the publication process could correct rather than reproduce the Anglophone cultural hegemony.